2016
DOI: 10.1186/s12909-016-0682-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peer-group size on the delivery of feedback in basic life support refresher training: a cluster randomized controlled trial

Abstract: BackgroundStudents are largely providing feedback to one another when instructor facilitates peer feedback rather than teaching in group training. The number of students in a group affect the learning of students in the group training. We aimed to investigate whether a larger group size increases students’ test scores on a post-training test with peer feedback facilitated by instructor after video-guided basic life support (BLS) refresher training. Students’ one-rescuer adult BLS skills were assessed by a 2-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Similar to prior years, the most common study populations were medical students (21/75; 28%) and residents (48/75; 64%) . Interestingly, this year only one study addressing medical students was highlighted for excellence, in contrast to prior years.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similar to prior years, the most common study populations were medical students (21/75; 28%) and residents (48/75; 64%) . Interestingly, this year only one study addressing medical students was highlighted for excellence, in contrast to prior years.…”
Section: Discussionmentioning
confidence: 92%
“…In response to a call for increased rigor in medical education research, EM education researchers increasingly apply thorough methodologic standards and evaluate higher level outcomes in their research studies. In 2016, there was a notable increase in the number of studies utilizing an experimental (hypothesis testing) design, 15 of 75 (20%), compared to nine of 611(5%) in 2015. Three of these studies with an experimental design were highlighted .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For PropG, the FI values were calculated using the true parameter values. The number of groups is usually determined so that each group comprises 3-14 members while maintaining the number as equal as possible for all groups [32], [72]- [74]. This experiment used G ¼ 3; 4; and 5 because the number of group members falls within this range when J 2 f15; 30g.…”
Section: B Evaluation Of Group Formation Methodsmentioning
confidence: 99%
“…Both the 2-student group and the 1-student group did not raise concerns regarding time management and e ciency. However, during the 2-student group session, we observed the potential for positive or negative peer interactions affecting learning experiences, which could lead to intervention heterogeneity within or between groups, and interfere with consistency and continuity of individualized instructor feedback [34]. A study that compared constant instructor feedback to intermittent feedback with peer feedback in chiropractic skill training demonstrated that constant feedback was advantageous for accurate skill acquisition and initial hands-on practice, while the intermittent feedback was advantageous for long-term skill retention [35].…”
Section: Curriculum Design Modi Cationsmentioning
confidence: 95%